On the variety of Mexico’s export goods - Ito, Tadashi (Estudios Económicos de El Colegio de México, 2015)
This paper examines the evolution of the variety of Mexico’s export goods using disaggregated trade data. Both the econometric estimation analyses using the raw data and the one using an improved version of Feenstra and Kee’s (2004, 2007) methodology proposed in this paper show that NAFTA membership does not enhance the variety of Mexico’s export goods. This finding contrasts with NAFTA’s positive association with the increase in export variety found in the literature